Striped transitory hyperpigmentation of the torso in a newborn. Case report. - Aher, S.; Phiske, M.; Jerajani, H.R. (European Journal of Pediatric Dermatology, 2010)
Striped hyperpigmentation of the torso is a very rare condition, with only three cases published worldwide in the last 43 years. It presents as bands of hyperpigmentation of the breast and abdomen which appear at birth and fade with normalization of the skin in few months. Here is reported a fourth case in a baby girl with protein energy malnutrition and epilepsy secondary to hypocalcemia.